2009
DOI: 10.1002/lt.21849
|View full text |Cite
|
Sign up to set email alerts
|

Donor and recipient selection leads to good patient and graft outcomes for right lobe split transplantation versus whole graft liver transplantation in adult recipients

Abstract: The outcomes of right lobe split (RLS) liver transplantation are variable in adult recipients. This report is an analysis of outcomes of our initial 5-year experience with the right lobe trisegment split graft. A retrospective analysis was performed of the recipient and graft outcomes from July 2002 to March 2007 of all adult recipients of RLS grafts versus recipients of whole grafts (WGs). All data were analyzed with Stata version 8 (Stata Corp., Texas). There were 43 (19.1%) RLS recipients and 182 (80.9%) WG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 20 publications
0
29
0
Order By: Relevance
“…Rates of vascular complications in adults vary in the literature between 2% and 11.6% for hepatic artery thrombosis and 0%‐2.3% for portal vein thrombosis . Doyle et al.…”
Section: Discussionmentioning
confidence: 99%
“…Rates of vascular complications in adults vary in the literature between 2% and 11.6% for hepatic artery thrombosis and 0%‐2.3% for portal vein thrombosis . Doyle et al.…”
Section: Discussionmentioning
confidence: 99%
“…(8, 14) Other studies have suggested that the diagnosis of hepatocellular carcinoma (HCC) may be also associated with poorer outcomes when accepting living-donor partial grafts,(1517) an association that has never been investigated in DD split grafts. Although more recent studies have shown improved outcomes in split liver transplantation, (8, 10, 13, 14, 18, 19) there has been no significant increase in its use over the past decade (1, 20)…”
Section: Introductionmentioning
confidence: 99%
“…In recent publications, results for SLT and whole liver transplantation have not differed in terms of initial graft function or long‐term outcomes. These data support SLT as a consistent tool for expanding the donor organ pool and reducing mortality on the waiting list 26‐29. However, some specific complications related to this technique may still be open to investigation.…”
Section: Discussionmentioning
confidence: 61%